2020
DOI: 10.7717/peerj.8937
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of brown anoles (Anolis sagrei) across a southern California county and potential interactions with a native lizard species

Abstract: The brown anole, Anolis sagrei, is a native species to the Caribbean; however, A. sagrei has invaded multiple parts of the USA, including Florida, Louisiana, Hawai'i and more recently California. The biological impacts of A. sagrei invading California are currently unknown. Evidence from the invasion in Taiwan shows that they spread quickly and when immediate action is not taken eradication stops being a viable option. In Orange County, California, five urban sites, each less than 100 ha, were surveyed for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Batista et al (2019) mentioned the capacity that this anole might have in displacing G. albogularis (Williams, 1969;Schoener et al, 2017). We discuss these behaviors as might be very similar to those mentioned by Pianka (1973) and Fisher et al (2019) that lead to competition between invasive and native species.…”
supporting
confidence: 55%
“…Batista et al (2019) mentioned the capacity that this anole might have in displacing G. albogularis (Williams, 1969;Schoener et al, 2017). We discuss these behaviors as might be very similar to those mentioned by Pianka (1973) and Fisher et al (2019) that lead to competition between invasive and native species.…”
supporting
confidence: 55%
“…Although it first arose on Cuba, the species now has the largest native range of any anole with natural diaspora populations found across islands of the northern Caribbean as well as coastal areas of Mesoamerica 21,22 . It is also a prolific invader with non-native populations established on many additional islands in the West Indies 23,24 , Costa Rica, multiple locations in both North 25 and South America 26,27 , as well as remote islands of the central Atlantic Ocean 28,29 , Hawaii 30 , Taiwan, and mainland Asia, Europe, and the Middle East. A recent analysis of genome-scale sequence data revealed that A. sagrei evolved on Cuba toward the end of the Miocene 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it first arose on Cuba 28 , the species now has the largest native range of any anole with natural diaspora populations found across islands of the northern Caribbean as well as coastal areas of Mesoamerica 28 , 29 . It is also a prolific invader with non-native populations established on many additional islands in the West Indies 30 , 31 , multiple locations in North 32 , South 33 and Central America 34 , as well as remote islands of the central Atlantic Ocean 35 , 36 , Hawaii 37 , Taiwan 38 , Asia, Europe, and the Middle East.…”
Section: The Brown Anolementioning
confidence: 99%